Perancangan electronic Museum (e-Museum) sebagai Media Promosi Kain Songket Khas Palembang - Vivi Sahfitri; Muhammad Nasir; Nyimas Sopiah (Politeknik Harapan Bersama, 2018)
Songket is a work of art which is a traditional fabric that is widely used in a variety of custom events in South Sumatera. Songket is made from a special yarn woven by using traditional weaving equipment. To generate a songket takes at least three months. This is causing a songket produced have the expensive price. In the community of South Sumatra songket is a must in custom events, among others, marriage ceremony, welcome the birth and Circumcision. Songket have various motives that have a specific name with the distinctive characteristics that differentiate between a songket with another. This research aims to design the application e-museum which can be a promotion media so the songket can widely know. The method used in building e museum Applications is ordinary Waterfall SDLC Models or linear sequential model. The result of the design can be implemented into the android-based applications.